STUDY ON FLAW DEPTH STATISTICS AND CORRESPONDING FATIGUE LIFE OF HELICOPTER ALUMINIUM ALLOY STRUCTURE - NI Yang; ZHOU ChuWei; YU JianJian; ZOU Jing (Jixie qiangdu)
Surface defect is the main fatigue failure source of helicopter metal dynamic components. Depth data of impact pit defects on surface of aluminum alloy critical dynamic parts of helicopter were collected,and statistical analysis was conducted. Statistic results show that the depth of impact pits obey the exponential distribution,and a standard size is confirmed according to the size coverage of 90%. The impact pit formation and fatigue crack initiation life of aluminum alloy（2 A12）commonly used in aviation were investigated using finite element method combined with continuum damage mechanics theory,and the rationality of the method was validated through fatigue test results. The study shows that a rational fatigue analysis of impact pit defect must take the local residual stress and plastic strain into account.